2014
DOI: 10.1161/jaha.113.000629
|View full text |Cite
|
Sign up to set email alerts
|

The TLR9 Ligand, CpG‐ODN, Induces Protection against Cerebral Ischemia/Reperfusion Injury via Activation of PI3K/Akt Signaling

Abstract: BackgroundToll‐like receptors (TLRs) have been shown to be involved in cerebral ischemia/reperfusion (I/R) injury. TLR9 is located in intracellular compartments and recognizes CpG‐DNA. This study examined the effect of CpG‐ODN on cerebral I/R injury.Methods and ResultsC57BL/6 mice were treated with CpG‐ODN by i.p. injection 1 hour before the mice were subjected to cerebral ischemia (60 minutes) followed by reperfusion (24 hours). Scrambled‐ODN served as control‐ODN. Untreated mice, subjected to cerebral I/R, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
55
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 48 publications
1
55
0
Order By: Relevance
“…Although immune activators have demonstrated success as prophylactic treatments for reduction of brain injury in experimental models of cerebral ischemia [13, 14, 24-28], their modulation of inflammation has dampened enthusiasm for clinical use. Systemic infection is often associated with poorer outcomes in stroke patients [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Although immune activators have demonstrated success as prophylactic treatments for reduction of brain injury in experimental models of cerebral ischemia [13, 14, 24-28], their modulation of inflammation has dampened enthusiasm for clinical use. Systemic infection is often associated with poorer outcomes in stroke patients [29, 30].…”
Section: Discussionmentioning
confidence: 99%
“…Although TLR9 plays important roles in immune responses, its potential benefit for the treatment of ischemic diseases independent of inflammation has recently attracted attention. It has been reported that CpG‐ODN preconditioning induces protection against cerebral and myocardial ischemia/reperfusion injury by activating the PI3K/Akt pathway (Cao et al, ; Lu et al, ). Moreover, CpG‐ODN postconditioning also improves cardiac function after myocardium ischemic/reperfusion injury by activating the TLR9/PI3K pathway (Kim et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Male C57BL/6 mice at 8–10 weeks of age were randomized to receive an intraperitoneal (i.p.) injection of CpG‐ODNs (1 mg/kg body weight) 2 hr prior to left anterior descending artery (LAD) ligation surgery as previously described (Lu et al, ). For certain experiments confirming the efficiency of lentiviral infection in vivo, lentiviruses were injected into the myocardium 3 days prior to MI induction to first upregulate or downregulate TLR9 expression.…”
Section: Methodsmentioning
confidence: 99%
“…TLR9's role in I/R is controversial. Previous studies have found that TLR9 activates the downstream PI3K pathway, and numerous studies have found that this is a protective pathway in cardiac muscle [13,[26][27][28][29][30]. However, TLR9 can also activate other signaling pathways, such as those found to have a role in myocardial injury.…”
Section: Cellular Physiology and Biochemistry Cellular Physiology Andmentioning
confidence: 99%